Upaya guru dan siswa dalam mengimplementasikan P5 melalui kegiatan pengelolaan sampah untuk mewujudkan sekolah berbasis Adiwiyata di MIN 1 Bojonegoro - Nurul Afidah; Dewi Niswatul Fithriyah; Siti Lutfiatul Muhamaliah; Ika Devi Ratna Ning Tias; Alfi Fakhriyyatun Nisrina (IKIP Siliwangi, 2026)
Abstrak This research abstract describes the efforts of teachers and students in implementing waste management learning theory based on the Project Strengthening the Pancasila Student Profile (P5) to support the Adiwiyata program at MIN 1 Bojonegoro. The P5 learning method, which prioritizes a sustainable lifestyle, is applied through the stages of introduction, contextualization, and evaluation, where students actively recognize, sort, and manage waste in the school environment directly. The teacher acts as a facilitator who motivates and guides students in the waste collection and management activities, so that students not only gain theoretical knowledge but also build awareness and character to care for the environment in accordance with Pancasila values. The implementation of this learning also supports the achievement of the Adiwiyata program's goals through increased student participation in maintaining the cleanliness and sustainability of the school environment. The results show an increase in students' environmental awareness and creativity in waste management, although there are still constraints such as limited facilities and teacher knowledge. Kata Kunci: Adiwiyata, Waste Management, P5-Based Learning, Pancasila Student Profile Abstrak Penelitian ini menggambarkan upaya guru dan siswa dalam menerapkan teori pembelajaran pengelolaan sampah berdasarkan Proyek Penguatan Profil Pelajar Pancasila (P5) untuk mendukung program Adiwiyata di MIN 1 Bojonegoro. Metode pembelajaran P5, yang mengutamakan gaya hidup berkelanjutan, diterapkan melalui tahap pengenalan, kontekstualisasi, dan evaluasi, di mana siswa secara aktif mengenali, memilah, dan mengelola sampah di lingkungan sekolah secara langsung. Guru bertindak sebagai fasilitator yang memotivasi dan membimbing siswa dalam kegiatan pengumpulan dan pengelolaan sampah, sehingga siswa tidak hanya memperoleh pengetahuan teoritis tetapi juga membangun kesadaran dan karakter untuk peduli terhadap lingkungan sesuai dengan nilai-nilai Pancasila. Pelaksanaan pembelajaran ini juga mendukung. Kata Kunci: Adiwiyata, Pengelolaan Sampah, Pembelajaran Berbasis P5, Profil Pelajar Pancasila